Cancer Risk in a Large Inception Systemic Lupus Erythematosus Cohort: Effects of Demographic Characteristics, Smoking, and Medications. Issue 12 (12th October 2021) - Bernatsky, Sasha; Ramsey‐Goldman, Rosalind; Urowitz, Murray B.; Hanly, John G.; Gordon, Caroline; Petri, Michelle A.; Ginzler, Ellen M.; Wallace, Daniel J.; Bae, Sang‐Cheol; Romero‐Diaz, Juanita; Dooley, Mary Anne; Peschken, Christine A.; et al.
Abstract : Objective: To assess cancer risk factors in incident systemic lupus erythematosus (SLE). Methods: Clinical variables and cancer outcomes were assessed annually among incident SLE patients. Multivariate hazard regression models (overall risk and most common cancers) included demographic characteristics and time‐dependent medications (corticosteroids, antimalarial drugs, immunosuppressants), smoking, and the adjusted mean Systemic Lupus Erythematosus Disease Activity Index 2000 score. Results: Among 1, 668 patients (average 9 years follow‐up), 65 cancers occurred: 15 breast, 10 nonmelanoma skin, 7 lung, 6 hematologic, 6 prostate, 5 melanoma, 3 cervical, 3 renal, 2 each gastric, head and neck, and thyroid, and 1 each rectal, sarcoma, thymoma, and uterine cancers. Half of the cancers (including all lung cancers) occurred in past/current smokers, versus one‐third of patients without cancer. Multivariate analyses indicated that overall cancer risk was related primarily to male sex and older age at SLE diagnosis. In addition, smoking was associated with lung cancer. For breast cancer risk, age was positively associated and antimalarial drugs were negatively associated. Antimalarial drugs and higher disease activity were also negatively associated with nonmelanoma skin cancer risk, whereas age and cyclophosphamide were positively associated. Disease activity was associated positively with hematologic and negatively with nonmelanoma skin cancer risk. Conclusion: Smoking is a key modifiable risk factor, especially for lung cancer, in SLE. Immunosuppressive medications were not clearly associated with higher risk except for cyclophosphamide and nonmelanoma skin cancer. Antimalarials were negatively associated with breast cancer and nonmelanoma skin cancer risk. SLE activity was associated positively with hematologic cancer and negatively with nonmelanoma skin cancer. Since the absolute number of cancers was small, additional follow‐up will help consolidate these findings.